Assessment of the cost-effectiveness of Australia's risk-sharing agreement for direct-acting antiviral treatments for hepatitis C: a modelling study - Dr Nick Scott; Ms Anna Palmer; Mr Tom Tidhar; Prof Mark Stoove; Dr Rachel Sacks-Davis; A/Prof Joseph S. Doyle; Dr Alisa Pedrana; Prof Alexander J. Thompson; Prof David P. Wilson; Prof Margaret Hellard (Elsevier, 2022)
Summary: Background: Hepatitis C elimination may be possible with broad uptake of direct-acting antiviral treatments (DAAs). In 2016 the Australian government committed A$1.2 billion for five years of unlimited DAAs (March 2016 to February 2021) in a risk-sharing agreement with pharmaceutical companies. We assess the impact, cost-effectiveness and net economic benefits likely to be realised from this investment. Methods: Mathematical modelling to project outcomes for 2016-2030 included: (S1) a counter-factual scenario (testing/treatment maintained at pre-2016 levels); (S2) the current status-quo (testing/treatment as actually occurred 2016-2019, with trends maintained to 2030); and (S3) elimination scenario (S2 plus testing/treatment rates increased between 2021-2030 to achieve the WHO elimination targets). Findings: S1 resulted in 68,800 new hepatitis C infections and 18,540 hepatitis C-related deaths over 2016-2030. The total health system cost (HCV testing, treatment, disease management) was A$3.01 billion and the cost of lost productivity due to absenteeism, presenteeism and premature deaths was A$26.14 billion. S2 averted 15,700 (23%) new infections and 8,500 (46%) deaths by 2030, with a total health system cost of A$3.48 billion, A$472 million more than S1 (A$1.65 billion more in testing/treatment but A$1.20 billion less in disease costs; A$5,752 per QALY gained from a health systems perspective). Productivity loss over 2016-2030 was A$19.96 billion, A$6.17 less than S1, making S2 cost-saving from a societal perspective by 2022 with a net economic benefit of A$5.70 billion by 2030. S3 averted an additional 10,000 infections and 930 deaths compared with S2 and increased the longer-term economic benefit. Interpretation: Five years of unrestricted access to DAAs in Australia has led to significant health benefits and is likely to become cost-saving from a societal perspective by 2022. Funding: Burnet Institute